Factors influencing ability to access to health care among sub-Saharan African migrants living in France : a comparison according to their HIV and HBV status - (:unkn) unknown (My University, 2018)
Immigrants from sub-Saharan Africa (SSA) are often exposed to periods of precariousness after arriving in France and are also one of the most affected populations by HIV and HBV infections. The aim of this thesis was to study the access to care of SSA immigrants according to their HIV or HBV status. The ANRS-Parcours survey was conducted among 2,468 SSA immigrants living in Paris area and the Baromètre santé 2010 among 27,653 people living in France. The Parcours survey used a biographical grid to collect indicators year after year analysed with a discrete-time logistic regression method. Sub-Saharan immigrants have access to health insurance coverage the year they arrived in France, but one in ten still did not have one three years after their arrival (more often in the absence of a permit of residence). They are more exposed to unmet health care needs than the rest of the population in France. This finding is aggravated by refusals to provide healthcare for participants covered by the specific health insurance for precarious or undocumented migrants and people living with HIV. The linkage to care takes place the year of the diagnosis. The likelihood of applying for a medical residence permit was higher among participants living with HIV. Social situations, which can change over time, affect the ability of immigrants to access health care. In the context of immigration, these social situations differ according to the reasons and conditions of arrival in France, depending on the status of the stay in France (having or not a residence permit, the right to work ...) and the way in which it evolves.
Keywords: African Research